Application of artificial intelligence in pain assessment - LIU Di; WANG Wenjun (Zhongguo linchuang yanjiu)
Artificial intelligence (AI) has been widely applied in the field of clinical medicine, including disease prediction and prevention, health management and monitoring, auxiliary diagnosis and treatment, medical imaging, drug development, etc. This article mainly summarizes the current application status of AI in pain assessment in China and internationally, explores its effectiveness in pain assessment, analyzes the problems and future development directions of AI in pain assessment, aiming to provide new ideas and references for the application of AI technology in the field of pain management in China.